2015
DOI: 10.1002/pon.3818
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in patients with cancer: the first year after cancer diagnosis

Abstract: Loneliness, in particular emotional loneliness, is a common problem in cancer patients, and its frequency changes considerably over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 32 publications
5
32
2
Order By: Relevance
“…64 Furthermore, a longitudinal study of 115 cancer survivors and noncancer controls found that loneliness predicted increases in fatigue in both groups over time. 65 Although we are characterizing loneliness here as a risk factor that may have predated the cancer diagnosis, it is also possible that cancer and associated symptoms, including fatigue, may precipitate feelings of social isolation 66 ; longitudinal research is required to disentangle these pathways.…”
Section: Lonelinessmentioning
confidence: 99%
“…64 Furthermore, a longitudinal study of 115 cancer survivors and noncancer controls found that loneliness predicted increases in fatigue in both groups over time. 65 Although we are characterizing loneliness here as a risk factor that may have predated the cancer diagnosis, it is also possible that cancer and associated symptoms, including fatigue, may precipitate feelings of social isolation 66 ; longitudinal research is required to disentangle these pathways.…”
Section: Lonelinessmentioning
confidence: 99%
“…For well‐being, we studied psychological well‐being and physical health with tools that are widely used in the literature. A more in‐depth description of the tools can also be found in previous publications from the Klimop study …”
Section: Methodsmentioning
confidence: 99%
“…A more in-depth description of the tools can also be found in previous publications from the Klimop study. 12,13,16 For psychological well-being, we considered depression, loneliness, and distress measured with the Geriatric Depression Scale for woman, range: 0-5 for men). 24 Dependence in 1 or more domains of ADL and IADL was defined as having an impairment.…”
Section: Well-beingmentioning
confidence: 99%
“…A diagnosis of cancer and subsequent treatment can have a substantial effect on the well-being of patients and their need for home care. As shown in our recent work, patients with cancer have increased levels of depression, loneliness, and increasing difficulties in cognitive functioning over the course of one year [ 10 , 11 ]. In light of this, we expect to see significant transitions in care after a diagnosis of cancer.…”
Section: Introductionmentioning
confidence: 99%